INFLUENCE OF MELATONIN ON THE REPRODUCTIVE SYSTEM IN DIFFERENT PERIODS OF WOMAN LIFE - Петров, Юрий Алексеевич; Шелемех, Кристина Евгеньевна; Купина, Анастасия Дмитриевна (Mother and Baby in Kuzbass, 2021)
The aim of research –The aim of the study is to analyze modern evidence-based sources of scientific literature containing data on the role of melatonin in the gynecological practice of a doctor.Materials and methods. An analysis of 25 sources of literature on this topic was carried out.Results. Based on the results of the analysis of scientific articles, relevant information has been updated and collected in this review. The role of melatonin in the development of the genitals, in the process of follicle maturation, in gametogenesis, fertilization and implantation, in the process of labor is described, and the connection with premenstrual dysphoric disorder and its place in the treatment of endometriosis, climacteric disorders, etc.Conclusion. The analysis shows that many valuable properties of melatonin make it promising to develop new approaches to its use as an element of therapy in obstetrics and gynecology.
Keywords: melatonin; sleep disturbance; menstrual cycle; ovulation; fertility; premenstrual syndrome; menopause syndrome